2004
DOI: 10.1038/sj.sc.3101657
|View full text |Cite
|
Sign up to set email alerts
|

Sexual issues in a sample of women with spinal cord injury

Abstract: Study design: Semistructured interview. Objectives: To assess the degree of participation in sexual intercourse of a sample of women with spinal cord injury (SCI) in our community, to establish to what extent their sexual lives have been affected in comparison to before the injury, and to search for those factors that may have a major influence on both aspects. Setting: Spinal Cord Injuries Unit, A Corun˜a, Spain. Participants: A total of 37 women, average age 40 years, time since onset average 10 years. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 24 publications
(54 reference statements)
3
70
3
1
Order By: Relevance
“…17,[20][21][22][23] Our study further revealed that these concerns are severe enough to prevent a considerable number of women from seeking sexual activity with a partner. It is possible that the fear of incontinence may contribute to psychological aspects of arousal as well.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…17,[20][21][22][23] Our study further revealed that these concerns are severe enough to prevent a considerable number of women from seeking sexual activity with a partner. It is possible that the fear of incontinence may contribute to psychological aspects of arousal as well.…”
Section: Discussionmentioning
confidence: 63%
“…In one study from Spain, 48% of the female subjects reported not using birth control. 21 A study from India found that 75% of the women with SCI did not use birth control. 22 In the US, one study found that 30% of women with SCI did not use birth control 17 and in our study 41% did not use birth control.…”
Section: Birth Control Use After Scimentioning
confidence: 99%
“…A study of 37 women indicated that these women are less likely to enter into a sexual relationship than any other group of SCI women (P ¼ 0.04). 41 Relationships Controversy exists over the importance of relationship status in rehabilitation to a satisfactory sexual life. Lack of partner availability is cited by 16.4% of a sample of SCI women as the cause of being sexually inactive (Po0.01).…”
Section: Psychosocial Factors Influencing Sexual Rehabilitationmentioning
confidence: 99%
“…A lack of respect of professional boundaries in the clinician-patient relationship is another neglected precipitating co-factor of FSD, especially for women who sought professional help in a vulnerable moment of their life [13,14] (see sub-chapter on Classification, etiology and key issues in FSD).They may behave as maintaining factors, through the most frequent mistake in the field of FSD: the diagnostic omission, which encompasses occasional or systematic diagnostic neglect, particularly in the area of biological/medical etiology of FSD [2,3,[4][5][6][10][11][12] and/or comorbidity between medical conditions and FSD [1-3,4-6,11-12, 15,16]. This chapter will discuss these three major areas of iatrogenic disorders, to open a mental window on the sexual scenario we clinicians often do not consider.The role of post-traumatic FSD will be briefly reviewed with a focus on spinal cord injuries [17][18][19][20], and ritual female genital mutilation (FGM) [21][22][23][24]. Sexual abuse, which may cause both a physical and emotional trauma, may be related to post-traumatic stress disorder and long term sexual disorders [25].…”
mentioning
confidence: 99%
“…The role of post-traumatic FSD will be briefly reviewed with a focus on spinal cord injuries [17][18][19][20], and ritual female genital mutilation (FGM) [21][22][23][24]. Sexual abuse, which may cause both a physical and emotional trauma, may be related to post-traumatic stress disorder and long term sexual disorders [25].…”
mentioning
confidence: 99%